A Review on Fire Fighter Robot Using Arduino with SMS Alert System (International Journal of Scientific Research in Science and Technology, 2025)
Fire accidents pose a significant threat to life and property, making early detection and rapid response crucial. This review for the design and development of a Fire Extinguisher Robot using Arduino Uno with an integrated SMS alert system. The robot is equipped with flame sensors to detect fire and automatically move towards the affected area. It utilizes DC motors for movement and a servo-controlled water spray mechanism for extinguishing the fire. Additionally, the system includes a GSM module, which sends real-time SMS alerts to predefined contacts upon fire detection, ensuring immediate human intervention. The robot operates autonomously, reducing human risk and enhancing fire safety measures. This cost-effective and efficient solution can be deployed in residential, industrial, and commercial environments to minimize fire-related damages.